PENINGKATAN KETERAMPILAN BERBICARA MELALUI MEDIA PERMAINAN TELEPON PADA ANAK TUNAGRAHITA - , MADECHAN (Pendidikan Luar Biasa, 2012)
Abstract; The purpose of this study is to determine whether these is an increase on speaking skills through the medium of telephone game for mild mentally retarded students class IV in SLB Tunas Harapan I Tembelang Jombang. The approach in this research is qualitative and this is a class action research which is done in two cycles with some steps; plan: to make preparation for action, implementation of the action, observation and evaluation and reflection. Research is conducted in class IV in SLB Tunas Harapan I Tembelang Jombang with 4 mild mentally retarded students. The results showed that media phone game can improve the mild mentally retarded students’ speaking skill that is above 75%. Based on the result of research it can be recommended that the media phone game can be used as a medium for students learning Indonesian because mild mentally retarded students are proven to work to increase understanding of children in conversational skill in daily life